Cultivating the culture of saving - UMP, PNC (2018)
Kuantan, 25 June – Realising the importance of cultivating a culture of savings through investment among undergraduates, Universiti Malaysia Pahang collaborates with Amanah Saham Nasional Berhad (ASNB) in organizing ASNB Financial Literacy Programme ‘Let’s Invest! 360 Days Investment’ that took place at Astaka Hall, UMP Gambang Campus recently.